Analysis Of Financial Of A Durian (Durio Zibethinus Murr) Nursery Bussines - Nursamsi Nursamsi (JASc (Journal of Agribusiness Sciences), 2019)
This study aims to determine how much income and financial viability of a durian nursery business located in Tanjung Morawa, Deli Serdang.  Method of location determination is done by purposive (intentional) is the consideration that area are carefully selected to match the expected conditions. Methods of sampling done by the Census methods namely in choosing the sample by taking all members of the population. This study aims to determine how the level of income, feasibility and effort to overcome the problems in breeding durian. The results showed that the average farm income durian seedlings Rp. 40.3125 million. Feasibility with a value of R / C 2.3> 1 and the B / C 1.3> 1 then the business is said to be worth the effort